Studi Kekuatan Eyebolt Pada Proses Pengangkatan Wellhead - Sandhy Purnomo Putra; Mufti Fathonah Muvariz; Naufal Abdurrahman Prasetyo (Jurnal Teknologi dan Riset Terapan (JATRA), 2020)
Wellhead is one of equipment used in oil and gas drilling process. In the process of moving wellhead from one place to another, often used lifting equipment such as eyebolt. The use of lifting equipment to assist the lifting process and to make it easier and safer. Eyebolt is a threaded hook that serves as a lifting tool. To know the safety of eyebolt when used, an analysis of the mechanical behavior of the eyebolt is required. In addition, the different angle of lift will affect the maximum stress, strain, displacement, and Factor of Safety (FOS) values significantly. To know the comparison of angle difference is done simulation on software Solidwork with value of 575.604 N. The simulation process is done with angle 35°, 45°, 60°. The maximum stress occurs at an angle 35 ° that is 195.765 and safest FOS occurs at an angle 60° that is 2.7, it means if angle of lifting larger are used safer.